THE ECONOMIC BENEFITS OF PHYSICAL FITNESS ON WORKFORCE PRODUCTIVITY - Ajaz Ahmad Dar; Irshad Ahmad Reshi (RADJA PUBLIKA, 2024)
This paper explores the economic benefits of physical fitness on workforce productivity, focusing on how improved physical health contributes to enhanced worker efficiency, reduced absenteeism, and lower healthcare costs. It examines various studies, workplace programs, and initiatives that promote physical fitness, highlighting the impact on employee performance and the broader economic outcomes for businesses and national economies. The paper also addresses the potential return on investment (ROI) for employers who invest in employee wellness programs, providing a comprehensive analysis of the economic advantages of promoting physical fitness in the workplace.